2017
DOI: 10.1002/2017gl073528
|View full text |Cite
|
Sign up to set email alerts
|

Mantle transition zone discontinuities beneath the Indochina Peninsula: Implications for slab subduction and mantle upwelling

Abstract: While the northward indentation of the Indian into Eurasian plates has been intensively investigated, its oblique subduction beneath the Indochina Peninsula (ICP) and the role it played on mantle structure and dynamics remain enigmatic. In this first regional‐scale receiver function study of the mantle transition zone (MTZ) discontinuities beneath the ICP and its surrounding areas, we stack ∼12,000 receiver functions recorded at 33 stations using a non–plane wave common‐conversion‐point stacking technique. Sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 48 publications
5
36
0
Order By: Relevance
“…Results from this study are consistent with the hypothesis that the upflow is capable of causing significant temperature anomalies in areas as deep as at least the upper MTZ. Thermal upwelling through a slab window has been proposed beneath some other areas such as the Indochina Peninsula (Yu et al, ) and SW China (Zhang et al, ) and is considered to be the upwelling component of a return flow system induced by sinking slab segments, as revealed by geodynamic modeling (Faccenna et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from this study are consistent with the hypothesis that the upflow is capable of causing significant temperature anomalies in areas as deep as at least the upper MTZ. Thermal upwelling through a slab window has been proposed beneath some other areas such as the Indochina Peninsula (Yu et al, ) and SW China (Zhang et al, ) and is considered to be the upwelling component of a return flow system induced by sinking slab segments, as revealed by geodynamic modeling (Faccenna et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous previous studies have demonstrated that the depth variations of the d 410 and d 660 can provide independent constraints on the depth extent of subducted cold slabs and high temperature anomalies (e.g., Anderson, ; Collier et al, ; Contenti et al, ; Li & Yuan, ; Liu et al, , ; Shearer & Masters, ; Wicks & Richards, ; Yu et al, ). The d 410 and d 660 are ubiquitous and well established in most global models and correspond to a globally averaged MTZ thickness of 250 km (Kennett & Engdahl, ; Kennett et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In d o c h in a P e n in s u la Sl ab R ol lb ac k Figure 10. A schematic cartoon showing the formation mechanisms of the observed seismic anisotropy beneath the Indochina Peninsula generated based on our observations and previous studies (Li et al, 2008;Pesicek et al, 2008;Yu et al, 2017b).…”
Section: Mantle Upwellingmentioning
confidence: 94%
“…While seismic tomography (e.g., Bijwaard et al, 1998;Li et al, 2008;Pesicek et al, 2008) and receiver function studies (Yu et al, 2017b) have demonstrated that the Indian slab has reached the mantle transition zone (MTZ), the key issue of whether the subduction is still active remains debated. A recent focal Geochemistry, Geophysics, Geosystems 10.1029/2018GC007474 mechanism study reveals that the P axis of earthquakes in the Benioff zone beneath the Burma Block has a predominantly NNE direction, which is similar to the direction of relative plate motion between the Indian and Eurasian plates, and argues against active subduction (Rao & Kumar, 1999).…”
Section: 1029/2018gc007474mentioning
confidence: 99%
“…Wang et al (2015) showed that late Cenozoic continental flood basalts, which originated directly above the edge of the Pacific stagnant slab beneath China, could be accounted for by subducted fluids triggering wet melting. Yu et al (2017) also provided evidence from seismic tomography for similar events beneath Southeast Asia.…”
Section: Big Wedges and Inward-facing Subductionmentioning
confidence: 88%